Estetica e Poetica in Giovan Battista Gelli : Gli Scritti Sull'arte e Su Dante. - Pini, Carolina (Berlin/Boston : Walter de Gruyter GmbH, 2023)
The series Classicism and Beyond / Il classicismo e oltre is dedicated to the dynamic dialectic of stabilization and destabilization of classicist norm structures in literature from the Italian Cinquecento to the European 18th century, in systematic, general approaches as well as readings of individual texts.
Intro -- Ringraziamenti -- Sommario -- 1 Introduzione: letteratura e vita civile in Giovan Battista Gelli -- 2 Il percorso laterale e capriccioso di Gelli: La Circe e I Capricci del Bottaio -- 3 Arte ed esegesi letteraria: esempi di un rapporto complesso -- 6 La produzione letteraria di Gelli nel dibattito del Cinquecento -- 5 Quellentafel per gli scritti sulle arti e sulle vite degli artisti -- 6 L'interesse estetico delle Letture -- 7 La ‹funzione Dante› nel Cinquecento -- 8 Giovan Battista Gelli e il ‹paraclassicismo› -- Appendice -- Bibliografia -- Indice dei nomi.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books